Cooperation between two periplasmic copper chaperones is required for full activity of the cbb3‐type cytochrome c oxidase and copper homeostasis in Rhodobacter capsulatus. Issue 2 (28th February 2016) - Trasnea, Petru‐Iulian; Utz, Marcel; Khalfaoui‐Hassani, Bahia; Lagies, Simon; Daldal, Fevzi; Koch, Hans‐Georg
Summary: Copper (Cu) is an essential micronutrient that functions as a cofactor in several important enzymes, such as respiratory heme‐copper oxygen reductases. Yet, Cu is also toxic and therefore cells engage a highly coordinated Cu uptake and delivery system to prevent the accumulation of toxic Cu concentrations. In this study, we analyzed Cu delivery to the cbb 3 ‐type cytochrome c oxidase ( cbb 3 ‐Cox) of Rhodobacter capsulatus . We identified the PCuA C‐like periplasmic chaperone PccA and analyzed its contribution to cbb 3 ‐Cox assembly. Our data demonstrate that PccA is a Cu‐binding protein with a preference for Cu(I), which is required for efficient cbb 3 ‐Cox assembly, in particular, at low Cu concentrations. By using in vivo and in vitro cross‐linking, we show that PccA forms a complex with the Sco1‐homologue SenC. This complex is stabilized in the absence of the cbb 3 ‐Cox‐specific assembly factors CcoGHIS. In cells lacking SenC, the cytoplasmic Cu content is significantly increased, but the simultaneous absence of PccA prevents this Cu accumulation. These data demonstrate that the interplay between PccA and SenC not only is required for Cu delivery during cbb 3 ‐Cox assembly but also regulates Cu homeostasis in R. capsulatus . Abstract : Copper transport and delivery to its cognate target enzymes is a highly coordinated process that depends on the intricate interaction between Cu transport proteins and Cu chaperones. The α‐proteobacterium Rhodobacter capsulatus contains two periplasmic Cu chaperones, SenC and PccA, which cooperate during Cu transfer from the P1B ‐type ATPase CcoI to the CuB‐heme b binuclear center of cbb 3 ‐type cytochrome oxidase and which are required for regulating Cu homeostasis.